Leveraging Islamic Finance for MSMEs as a Tool for Financial Inclusion, Development, and Growth in Underbanked Countries - Sazir Nsubuga Mayanja (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
There are over 500 million MSMEs worldwide, of which 60% are in emergent economies. A third of these are in Muslim countries. In many of these countries, individuals and enterprises are excluded from the formal financial system, whether voluntarily or not. The MSMEs are financially un-served or underserved. Governments and multilateral agencies like the International Monetary Fund (IMF) the World Bank and their affiliates note that Islamic finance has grown rapidly and can be leveraged for strong economic growth. The study was intended to establish the major reasons for financial exclusions being more pronounced in some regions than in others, and whether this can be resolved by the new, financial technology, Islamic finance. The major finding is that religion plays a key role and that Islamic finance can be one of the tools to redress the situation. The methodology used has been a rigorous review of articles in credible peer- reviewed journals, conference papers, books, research projects, and the internet. The data gathered thus has been synthesized, correlated, and conclusions drawn.